Population and Activities of Peatland Microorganisms on Oil Palm Plantation based on Soil Depth and Age of Plant - Oktanis Emalinda (Department of Crop Science, Faculty of Agriculture, Andalas University, 2021)
Population and activity of soil microorganisms can be used as indicators in soil management. This research aims to examine the population and activity of peat soil microorganisms based on the depth and age of oil palm plantations. This research is located in Katapiang, Batang Anai Subdistrict, Padang Pariaman District, which peat land is used for palm oil plantations and it getsa minimal plantation management. The research uses survey method in four stages: preparation, pre survey, main survey and sampling, laboratory analysis and data processing. Samples taken on peat land that planted with palm oil from ages 0-5 years, 5-10 years, 10-15 years, and samples from natural peatlands. Sampling at depths of 0-20 cm, 20-40 cm, and 40-60 cm. From the data analysis, the soil microorganisms population is decreasing with the increase of palm oil plantations age. The bacterial and fungal populations mostly are on the surface. Meanwhile, the highest activity of microorganisms is on 5-10 years palm oil land. Phosphate solvent bacteria mostly found in 5-10 yearspalm oil. Ground water level, water content and soil pH also affect the population and activity of soil microorganisms.